Studi Komparasi Beton Menggunakan Berbagai Merk Semen dengan Mutu Beton Struktural - Ahmad, Hilfi Harisan; Hamduwibawa, Rofi Budi; Fiendyo, Muhammad Haykal; Malatania, Lala Arum (Politeknik Negeri Lhokseumawe, 2024)
Development in the field of structures is currently experiencing very rapid progress, which is taking place in various fields, such as high-rise buildings, bridges, towers and others. Concrete is a material for making structures that is in demand because of its many advantages compared to other materials. Concrete quality, as an indicator of quality, is always a major concern during construction. It is hoped that this research can obtain concrete strength levels based on the use of materials available around the community in general. The concrete produced complies with applicable quality standards. parameters for using the Y cement, X cement and Z cement, the use of these cement brands is based on the fact that these three brands are in accordance with SNI 7064-2014 and these three cement brands have been widely circulated where the author lives and have been used by many groups, both for small and large jobs. big. The quality of concrete used in this research is K300 or f'c 24.9 MPa. The Fc' value limits used according to SNI 2847-2019 range from 17 MPa to 35 MPa. Concrete testing uses SNI 1974-2011 guidelines. the results achieved at 28 days of age ranged from 24.32 MPa to 30.83 MPa. The results of this research do not look for which brand is the best, the size of the value obtained is not proof that a particular brand always has good results, but many factors influence the value obtained. Further research is needed on the use of this brand of cement to get more varied results.